A systematic mapping procedure based on the Modified Gaussian Model to characterize magmatic units from olivine/pyroxenes mixtures: Application to the Syrtis Major volcanic shield on Mars. Issue 8 (22nd August 2013) - Clenet, Harold; Pinet, Patrick; Ceuleneer, Georges; Daydou, Yves; Heuripeau, Frédérick; Rosemberg, Christine; Bibring, Jean‐Pierre; Bellucci, Giancarlo; Altieri, Francesca; Gondet, Brigitte
Abstract: [1] Clenet et al. (2011) have developed an adapted version of the Modified Gaussian Model (MGM). The improvements allow the characterization of spectra of olivine‐pyroxene(s) mixtures, addressing both modal composition and individual minerals chemical composition. This version of MGM is fully automated and operational with large amounts of hyperspectral imaging data. Two natural cases are considered. The first one is the Sumail massif in the Oman ophiolite (Earth). Based on our approach applied to HyMap data, two contrasted lithologic units are mapped: the mantle, which is harzburgite dominated, and the crust made of gabbros and clinopyroxene‐rich cumulates, with spectral variations interpreted in terms of pyroxenes chemical compositions. Once this new MGM mapping approach has been validated on a controlled natural situation, we map the distribution of mafic assemblages across the Syrtis Major volcano on Mars using a visible and near‐infrared (VNIR) ‐ short wave infrared (SWIR) Observatoire pour la minéralogie, l'eau, les glaces et l'activité (OMEGA) / Mars Express (MEx) mosaic. Our results are in agreement with previous work but olivine appears to be more abundant than previously estimated in the central part of the volcanic edifice, especially in ternary mafic assemblages (augite, olivine, enstatite). Based on these results, we propose a possible scenario for the igneous (and thus thermal) evolution of the Syrtis Major region. Surrounding terrains have formed first and local heterogeneity can be observed between northern and southern areas of the Noachian crust. We also observe variations in the mineral assemblages within Syrtis Major lavas, which can be interpreted in terms of differentiation from a common parent melt and/or of a progressive evolution of the mantle source composition and temperature. Key Points: MGM systematic mapping on Syrtis Major to characterize mafic minerals mixtures Olivine and pyroxenes mixture is detected in the central lavas of the volcano Pyroxenes have chemical compositions spanning the enstatite‐augite range